Network security and its impact on business strategy - Oncioiu, Ionica, 1972- (Advances in information security, privacy, and ethics (AISPE) book series., 2019)
"This book examines the impact of m-commerce, m-learning, and m-knowledge management technologies on organizations, such as online stores, higher education institutions, multinational corporations, and health providers"--